2021
DOI: 10.3390/cancers13061209
|View full text |Cite
|
Sign up to set email alerts
|

Complement in Tumourigenesis and the Response to Cancer Therapy

Abstract: In recent years, our knowledge of the complement system beyond innate immunity has progressed significantly. A modern understanding is that the complement system has a multifaceted role in malignancy, impacting carcinogenesis, the acquisition of a metastatic phenotype and response to therapies. The ability of local immune cells to produce and respond to complement components has provided valuable insights into their regulation, and the subsequent remodeling of the tumour microenvironment. These novel discoveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 313 publications
(411 reference statements)
1
17
0
1
Order By: Relevance
“…In our data, the fact that no change was observed in parallel in lymph nodes could be explained by the finding that activation of the complement cascade resulted in rapid disappearance of C9 from the plasma and accumulation in the spleen [47]. However, although the reversion induced by curcumin treatment was not complete, a common effect in spleen and lymph nodes was observed for another member of the complement system, C3, consistent with its known role in both the classical and alternative pathways [48]. Regarding transgelin-2, Ma and colleagues have revealed that the gene encoding for this protein belonged to a group of fifteen genes involved in curcumin's therapeutic effect against human tongue cancer [41].…”
Section: Discussionsupporting
confidence: 56%
“…In our data, the fact that no change was observed in parallel in lymph nodes could be explained by the finding that activation of the complement cascade resulted in rapid disappearance of C9 from the plasma and accumulation in the spleen [47]. However, although the reversion induced by curcumin treatment was not complete, a common effect in spleen and lymph nodes was observed for another member of the complement system, C3, consistent with its known role in both the classical and alternative pathways [48]. Regarding transgelin-2, Ma and colleagues have revealed that the gene encoding for this protein belonged to a group of fifteen genes involved in curcumin's therapeutic effect against human tongue cancer [41].…”
Section: Discussionsupporting
confidence: 56%
“…In cancer research, the therapeutic aspects of the complement system emerged as a consequence of unveiling its effect on TME components. Complement-related therapies may represent a promising strategy to overcome the failure of response to immunotherapy in different solid tumors including CRC ( 18 ).…”
Section: Therapeutic Aspects Of the Complement System In Crcmentioning
confidence: 99%
“…In the last few years, a limited number of reviews and original studies have discussed the potential use of complement in therapeutics of different cancers ( 17 , 18 , 121 , 122 ). Since the role of the complement system remains controversial, whether it is pro- or anti- tumorigenic, studies suggested suppressing the complement activation as a novel strategy for cancer treatment, probably using C5aR and C3aR blockers ( 25 ).…”
Section: Therapeutic Aspects Of the Complement System In Crcmentioning
confidence: 99%
See 2 more Smart Citations